Spiroindoline-Capped Selective HDAC6 Inhibitors: Design, 2 Synthesis, Structural Analysis, and Biological Evaluation - Zisterer, Daniela; Kelly, Vincent; O'Sullivan, Jeffrey (My University, 2020)
Histone deacetylase inhibitors (HDACi) have emerged as promising therapeutics for the treatment of neurodegeneration, cancer, and rare disorders. Herein, we report the development of a series of spiroindoline-based HDAC6 isoform-selective inhibitors based on the X-ray crystal studies of the hit 6a. We identified compound 6j as the most potent and selective hHDAC6 inhibitor of the series. Biological investigation of compounds 6b, 6h, and 6j demonstrated their antiproliferative activity against several cancer cell lines. Western blotting studies indicated that they were able to increase tubulin acetylation, without significant variation in histone acetylation state, and induced PARP cleavage indicating their apoptotic potential at the molecular level. 6j induced HDAC6-dependent pSTAT3 inhibition.
PUBLISHED
Keywords: HDAC inhibitors; Spiroindoline; STAT3; Cancer therapy; HDAC6; HDAC6; Cancer